(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The essay aims to analyse the role of the Constitution and the constitutional principles in determining the regulations of the voluntary termination of pregnancy. For this purpose, the essential role played by the Constitutional Court will be taken into account, also in the light of the scientific progress and the evolution of social awareness.